Innovation strategies and firm growth - Stefano Bianchini; Gabriele Pellegrino; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
In this work, we explore the relations between sales growth and a set of innovation indicators that capture the different sources, modes and results of the innovative activity undertaken within firms. We exploit a rich panel on innovation activity of Spanish manufacturing firms, reporting detailed CIS-type information continuously over the period 2004-2011. Standard GMM-panel estimates of the average effect of innovation activities reveal significant and positive effect for internal R&D, while no effect is found for external sourcing of knowledge (external R&D, acquisition of embodied and disembodied technologies) as well as for output of innovation (process and product innovation). However, fixed-effects quantile regressions reveal that innovation activities, apart from process innovation and disembodied technical change, display a positive effect on high-growth performance. Finally, we find evidence of super-modularity of the growth function, revealing complementarities of internal R&D with product innovation, and between product and process innovation.
Keywords: C21; D22; O31; O32; 330; firm growth; product and process innovation; internal and external R&D; embodied and disembodied technical change; fixed-effects quantile regressions; complementarity